STUDIES OF PLATELET AND LEUKOCYTE ATTACHMENT TO WHOLE HUMAN ARTERY SEGMENTS - Schorer, Anna E; Johnson, Debra J; White, James G (Thrombosis and Haemostasis, 1987)
Activation of endothelial cells (EC) by inflammatory stimuli can result in heightened procoagulant properties towards coagulation proteins. These alterations can be readily studied in existing tissue culture models which lack a component of flow (shear). It is generally believed that thrombosis in the venous (low shear) regions of the vasculature are relatively dependent upon the coagulation proteins, whereas clots in the arterial system (high shear) are more dependent upon platelet plugs. Adhesion of the platelets to vessel wall elements under controlled conditions of flow have also been addressed in a number of models, such as the "Baumgartner chamber". In this model, blood or platelets are perfused over denuded, everted vessel segments, usually rabbit aortae. We have modified this model to study attachment of platelets to arterial segments of human origin which retain an intact layer of native EC. Arteries are aseptically removed from umbilical cords, trimmed, washed, and gently everted. The segments are placed in Medium 199 with 20% calf serum and standard growth supplements. After 4-10 days, these segments are placed on rods and perfused with whole citra-ted blood (800 sec−1). Such segments permit attachment of single platelets, but not platelet aggregates. Identical segments from which EC are mecnanically removed promote attachment of large (>5 cell) platelet thrombi. Endothelialized segments which are pre-treated (16 hours) with thrombin or phorbol myristate acetate show reduced attachment of platelets. In selected regions, clusters of leukocytes are attached to these segments, either upon or beneath the still- confluent layer of EC. Artery segments treated with bacterial endotoxin (1 mcg/ml) for 90 minutes, by contrast, show enhanced attachment of platelets, both as a monolayer of platelets and as small (2-5 cell) aggregates. This novel application of the Baumgartner assay demonstrates that platelet and leukocyte attachment to confluent EC may occur under conditions of moderate shear, and may be regulated in part by EC, which in turn may be modulated by exogenous mediators.